Web-Portal on Indigenous Plants for Awareness Creation among Younger Generations - Zainal Abidin, Nuraina Aqilah (IRC, 2020)
Malaysia’s flora and fauna are among the most diverse in the world. Malaysia’s rainforests turn out to be perfect conditions for flourishing plant growth especially indigenous plants. Indigenous plants are native plant species, originated from a particular region. They can be considered as our country’s National Natural Treasure. In Malaysia, Sarawak and Pahang are among the states that are blessed with abundance of natural resources such as indigenous plants and most of the indigenous community there still use them in their daily lifestyle. In many parts of the world, people living in the city area, rural area and indigenous communities are facing tremendous cultural, economic and environmental changes, which contribute to weaken their knowledge base. Nowadays, it is not common for the younger generation of Malaysia to be aware regarding the importance and benefits of indigenous plants. The younger generation are not familiar with plants use to be common to all, let alone those indigenous plants. In this dissertation, the statement above will be further discussed upon. This project is about creating a web-portal on indigenous plants for awareness creation among younger generations in hope that the younger generation nowadays will gain new knowledge and cherish the national treasure of their home-country.